2016
DOI: 10.14202/vetworld.2016.1400-1406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Acacia nilotica pod meal on hematobiochemical profile and fecal egg count in goats

Abstract: Aim:This study was conducted to observe the effect of feeding Acacia nilotica pod meal on hematobiochemical profile and gastrointestinal parasitic load in growing goats.Materials and Methods:To experiment was conducted for a period of 3-month on 24 male goats (3½ month old, average body weight [BW] 6.50±1.50 kg), distributed into four groups of six animals each. The experimental animals were fed graded level of A. nilotica pod meal (0%, 10%, 20% and 30%) mixed in concentrate mixture equivalent to tannin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Recently, Paswan et al. () reported that A. nilotica pods meal at a moderate level (20% of total DMI) did not inhibit voluntary feed intake in goats rather it increases the feed intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Paswan et al. () reported that A. nilotica pods meal at a moderate level (20% of total DMI) did not inhibit voluntary feed intake in goats rather it increases the feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Acacia nilolica is rich in tannins and other secondary compounds which can be controlled and reduced by subjecting them to process in various ways like boiling pods in water, adding charcoal to pods or by sun‐drying (Sikosana, ). Moreover, A. nilotica was found to increase the performance in goats (Uguru, Lakpini, Akpa, & Bawa, ) and has also good health impact via reducing faecal nematodes and protozoan egg counts (Paswan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…57 There was evidence that a gradient concentration of tannin ( Acacia nilotica ) could decrease serum creatinine significantly when over 1.19% dietary tannin was fed to goats. 58 Yet the reduction of creatinine in the TA and GSPE groups did not reach a significant level in the study, and the lower tannin level (0.5%) was probably the cause.…”
Section: Discussionmentioning
confidence: 73%
“…The results showed 20-100% mortality in the tested rats. For safety uses of medicinal herbs, [53] mentioned that most herbal dosages for adults are calculated on the basis of a 150 lb (70 kg). According to this, if the latter dose of acacia nilotica fruits calculated to adult human it is 35-350 g/day which are very high doses & far from the reality.…”
Section: Toxicity Studies On Acacia Nilotica Fruitsmentioning
confidence: 99%